Composites of MWCNTS and metal oxides(hydroxides) prepared via fenton reaction and their applications in LIBS and OER - Liu, Xiaojuan (2016)
With the rapid development of society, the soaring consumption on fossil energy and the heavy environmental deterioration, looking for sustainable and clean energy such as solar, wind, hydrogen, has become the top priority for improving the environment pollution and accelerating the economic growth. However, the time and region limitation unable to meet the regional demand of energy, therefore, the research of effective energy storage and conversion (EESC) devices has become the research priorities. Lithium ion batteries (LIBs) as one of the EESC devices have been studied by many research groups. Oxygen evolution reaction (OER), as the anode reaction in water splitting and positive electrode charging reaction in metal-air batteries, plays a crucial role in the field of EESC. Composites of carbon material and metal oxide (or hydroxide) with their intrinsic properties can be used in the above two field as an anode or an electrocatalyst, respectively. But the common preparation method published in most articles for this type of composites usually contains two steps: first, the carbon materials should be oxidized to introduce oxygen functional groups to react with metal ions, then followed with hydrothermal reaction to make sure the reaction happened between oxidized carbon material and metal ions and finally to generate the composites of carbon materials and metal oxides. Herein, Fenton reaction with Fenton reagents (Fe2+-H2O2) was used to synthesize composites of carbon material and metal oxides (or hydroxides). Because carbon material could be firstly oxidized by Fenton reagents and secondly Fe3+ in Fenton reagents can be used as iron sources. Hence, in this work, composites of Fe(OH)3 and expandable graphite nanosheets (Fe(OH)3/EG), Fe(OH) 3 and multi-walled carbon nanotubes (Fe(OH)3/MWCNTs), Fe2O3/MWCNTs, NiFe layered double hydroxides and MWCNTs (NiFe LDHs/MWCNTs) were prepared by Fenton reaction with sonication assistance. and Fe2O3/MWCNTs used as anode material in LIBs and NiFe LDHs/MWCNTs used as electrocatalyst for OER were investigated, respectively. influence on particle size and crystal structure of metal hydroxide in the process of crystallization, hydrothermal treatment was applied after Fenton reaction which was named as EG-F-H and MWCNTs-F-H, respectively. However, the results show that MWCNTs-F without hydrothermal reaction has higher capacities than that of MWCNTs-F-H. Because the particle size of metal hydroxide on MWCNTs-F surface is smaller than that of MWCNTs-F-H, and part of metal hydroxide particles located on the surface of MWCNTs-F could drop down to the solution during the hydrothermal reaction. And EG-F also show a higher capacity than that of EG-F-H. In the Fenton reaction process, sonication was used to enhance the reaction. Hence, the optimized sonication time was also selected according to the properties of composites and the optimized sonication time is 3h. Composite of Fe2O3/MWCNTs was prepared by Fenton reaction with a heat treatment (200℃) to ensure that Fe(OH)3 was transferred to Fe2O3. It was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR) etc. The XRD and Selected area electron diffraction (SAED) display that Fe2O3 in the composite has an amorphous structure, and SEM shows Fe2O3 nanoparticles load on MWCNTs surface. This indicates that MWCNTs was oxidized by Fenton reagents and introduced oxygen functional groups with negative charge. The electrostatic interaction between MWCNTs and iron ions with positive charge finally promote the production of composite of Fe2O3/MWCNTs. The electrochemical measurement for composite used as an anode in LIBs shows that the composite of Fe2O3/MWCNTs exhibits an excellent cycle performance with a reversible capacity of 900 mAh/g at 500 mA/g after 500 cycles and a high rate capability of 785 mAh/g at a high current density of 2 A/g. It is ascribed that the random ordered amorphous structure of Fe2O3 decreases the ion pathway and increase the diffusion of Li ions. The MWCNTs substrate provides an electronic path way and promotes the charge transportation and enhances the rate capability. Herein, NiFe LDHs/MWCNTs as an electrocatalyst used as a type of EESC was also synthesized by obtained by Fenton reaction followed with a coprecipitation process. Ni ions was simply added into the suspension of MWCNTs after the process of Fenton reaction under pH=9-10, NiFe LDHs/MWCNTs was obtained. XRD and SAED images indicate that the composites have low crystalline structure because the temperature and pressure used in this reaction is room temperature and atmospheric pressure with short reaction time. Linear sweep voltammetry (LSV), Chronopotentiometry (CP) and multi-CP were used to test their electrocatalytic properties. The results show that F(3-1)3 (named based on total ration and molar ratio between Ni: Fe explained in experimental part) displays excellent electrocatalytic properties with small overpotential of 212 mV and 283 mV at 10 mA/cm2 and 100 mA/cm2, respectively, and a few Tafel slope of 64.46 mV/dec. The outstanding electrocatalytic performance is traced to the low crystal structure of NiFe LDHs nanoparticles which could expose more active sites and facilitate the reaction between electrode and electrolyte. MWCNTs is also responsible for the excellent electrocatalytic properties, because MWCNTs enhance the conductivity of composites and improve the kinetic of OER.